1986
DOI: 10.2527/jas1986.632586x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Marginal Selenium Deficiency and Winter Protein Supplementation on Growth, Reproduction and Selenium Status of Beef Cattle

Abstract: Seventy-two Hereford X Simmental cows, averaging 498 kg in body weight and 5.2 yr of age, were used in a 2-yr study to ascertain if selenium (Se)-vitamin E (E) injections and winter protein supplementation would affect growth, reproduction and health of beef cattle maintained year-round on feedstuffs marginally deficient in Se (.03 to .05 mg/kg). Cows received either no injection or a mixture of 30 mg Se (as sodium selenite) and 408 IU E injected subcutaneously beginning 3 to 4 mo prepartum and at 60-d interva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
33
0
5

Year Published

1990
1990
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 17 publications
4
33
0
5
Order By: Relevance
“…There were no differences (P>0.05) in ADG and feed conversion. Several studies have shown an increase in ADG with Na 2 SeO 3 injections (Spears et al 1986, Castellan et al 1999 or no response when supplemented with the Se boluses release (Gunter et al 2003) or directly in cattle feed (Lawler et al 2004) and lambs (Vignola et al 2009). Contrary to our results, Kumar et al (2009) found a positive effect on growth performance of the lambs.…”
Section: Growth Performancementioning
confidence: 99%
“…There were no differences (P>0.05) in ADG and feed conversion. Several studies have shown an increase in ADG with Na 2 SeO 3 injections (Spears et al 1986, Castellan et al 1999 or no response when supplemented with the Se boluses release (Gunter et al 2003) or directly in cattle feed (Lawler et al 2004) and lambs (Vignola et al 2009). Contrary to our results, Kumar et al (2009) found a positive effect on growth performance of the lambs.…”
Section: Growth Performancementioning
confidence: 99%
“…A study with beef cows and calves fed on feeds marginally deficient in Se indicated that bimonthly Se-vitamin E injections reduced calf death losses (4·2 % v. 15·3 %) from birth to weaning (Spears et al 1986). Most of the deaths in the study were attributed to diarrhoea and subsequent lack of thrift.…”
Section: Disease Resistancementioning
confidence: 99%
“…( Spears et al, 1986), 셀레늄 결핍시 체중저하 및 폐사가 우려되고 과잉섭취 시 식욕저하를 유발할 수 있다 (Rosenfeld and Beath, 1964). II.…”
unclassified